Amputation demographic assessment at Saiful Anwar hospital: 5 years of study - Persada Isma, Satria Pandu; Irsan, Istan Irmansyah; Purantoro, Fiski; Putera, Marvin Anthony (International Journal of Research in Medical Sciences, 2020)
Background: Loss of limbs occurs due to different causes and has increased in many countries. This has large economic, physical and social impacts. This study investigates the demographics of patients undergoing amputation at Saiful Anwar Hospital Malang. Methods: This retrospective study was done from January 2014 to December 2018. The patient demographics included age, sex, organ amputation, etiology and amputation level. A total of 479 patients were studied in the study. Results: The average amputation value was 95.8 per year and varied from 72 to 134. The average age of the subjects was 44 years. Of all patients, 311 were male (64.93) and 168 women (35.07), 236 of amputations (49.27%) were major and 243 (50.73%) were minor. Conclusions: The main cause of amputation is trauma and most often is the amputation of the lower extremity. In trauma patients, the average age is 29 years. This result shows the same characteristic in the cause of amputation as in many other developing countries based on some studies. Trauma is the most common cause of amputation in Malang.